2018
DOI: 10.1002/ccr3.1669
|View full text |Cite
|
Sign up to set email alerts
|

Penile lesion in a dialysis patient: Time to get an X‐ray

Abstract: Key Clinical MessageCalciphylaxis or calcific uremic arteriolopathy is a rare and serious disorder typically seen in patients with end‐stage renal disease that manifests as skin ischemia and necrosis and histologically characterized by calcification of dermal arterioles. Penis is a rare site of involvement and biopsy is not typically recommended, making the diagnosis clinico‐radiologic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The delayed diagnosis caused by clinicians' insufficient understanding of calciphylaxis contributes to this serious illness condition. The predilection sites of calciphylaxis are soft and fatty tissues, for instance, the abdomen, buttocks and thighs [1,4], although necrosis of the extremities such as fingers [15] and penises [16,17] is also constantly reported. Davis et al conducted a literature review and found that obesity was identified as a risk factor in six of the eight studies reviewed [18].…”
Section: Discussionmentioning
confidence: 99%
“…The delayed diagnosis caused by clinicians' insufficient understanding of calciphylaxis contributes to this serious illness condition. The predilection sites of calciphylaxis are soft and fatty tissues, for instance, the abdomen, buttocks and thighs [1,4], although necrosis of the extremities such as fingers [15] and penises [16,17] is also constantly reported. Davis et al conducted a literature review and found that obesity was identified as a risk factor in six of the eight studies reviewed [18].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is determined after reviewing the patient's health history and a focused wound assessment finding of classic painful ulcerated lesions that are covered by a black eschar. While some healthcare providers still use skin biopsy as a diagnostic tool, it is no longer the gold standard for diagnosing penile calciphylaxis 8,9. In fact, there is some debate about its use.…”
Section: Diagnosismentioning
confidence: 99%
“…While some healthcare providers still use skin biopsy as a diagnostic tool, it is no longer the gold standard for diagnosing penile calciphylaxis. 8,9 In fact, there is some debate about its use.…”
Section: Wwwnursing2021commentioning
confidence: 99%